Diachronic Variation in the Omani Arabic Vernacular of the Al-ʿAwābī District - Morano, Roberta (Open Book Publishers, 2022)
In this monograph, Roberta Morano re-examines one of the foundational works of the Omani Arabic dialectology field, Carl Reinhardt’s Ein arabischer Dialekt gesprochen in ‘Oman und Zanzibar (1894). This German-authored work was prolific in shaping our knowledge of Omani Arabic during the twentieth century, until the 1980s when more recent linguistic studies on the Arabic varieties spoken in Oman began to appear.